Study of bilinear elastic horizontal displacement spectrum models. (June 2022) - Wang, Guotao; Hu, Bin; Cai, Jian
Abstract: To obtain elastic horizontal displacement spectra for different damping ratios for use in displacement-based seismic design, the influences of the moment magnitude, fault distance, and site class on the 5%-damped elastic horizontal displacement spectrum are first investigated using the ASK14 ground motion prediction equation (GMPE). Then, bilinear displacement spectrum models for different damping ratios are proposed based on the statistical characteristics of the displacement spectra of strong motion records with the principle of retaining the major influencing factors and neglecting the minor ones, and the models are used to describe uniform hazard displacement spectra for a point source site with a return period of 475 years. Finally, the method for implementing the proposed models in practical applications is discussed. The results of the study show the following. The moment magnitude is the main factor affecting the shape of the displacement spectrum. The proposed bilinear displacement spectrum models can reflect the influence of the moment magnitude, reflect the statistical characteristics of the displacement spectra of the actual strong motion records, and well describe the uniform hazard displacement spectra of the point source site with a return period of 475 years. The zoning map of the two spectral displacements and the corresponding site amplification factors and damping scaling factors of the bedrock site at each seismic hazard level are provided to enable the implementation of the proposed bilinear displacement spectrum models in practical applications.